Individual vs. communal identity – individual tumuli burials in the Eastern Hallstatt Circle - Potrebica, Hrvoje (Array, 2007)
Most of the cultural groups that belong to the complex that we call “ Eastern Hallstatt Circle” practice tumuli burials. With notable exception of groups such as Dolenjska or Budinjak, where multiple burials are more rule than the exception, in most cases such tumuli contain single burial. In most of the cases category of “ single” was identified with “ individual” burials and elements of the grave inventory in such units were interpreted as related to individual identity of a deceased person. In cases like Kleinklein where large number of burials testify that majority of population was buried under tumuli, following more or less same ritual, that identification may seem plausible. However, on many sites number of burials under tumuli is obviously much smaller than general population of the community in question, and that disproportion suggests that burials under tumuli must have been, at least in some part, determined by elements related more to the identity of the community than to the identity of the buried individuals.